Peranan Pekerja Sosial Sebagai Broker Terhadap Anak Jalanan Di Panti Sosial Bina Remaja Taruna Jaya 2 - Shabrina Afifah Rasyid; Muhammad Sahrul (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Street children in the DKI Jakarta area have social problems, they must be trained by professional experts in institutions, therefore social workers are part of the work that is carried out every day to serve dozens, even hundreds of social assistance participants. Good human resource management is needed to ensure that it does not have an impact on increasing social problems on the streets. Therefore, one of the efforts of social workers to properly implement the roles of social workers, one of which is broker. This research aims to determine the causes of children living on the streets, to determine the role of social workers at the Bina Pemuda Taruna Jaya 2 Social Institution and to determine the social functioning of street children at the Taruna Jaya Youth Development Institution 2. This research uses descriptive qualitative research methods. Data collection was carried out by means of interviews, observation and documentation. And determining informants uses purposive sampling. To overcome the social problems of street children, as a social worker, he carries out general roles at the Bina Pemuda Taruna Jaya Social Institution 2. The services provided by the institution to improve the social functioning of street children are in the form of administrative services, health services, family services, practical skills education services , there is social counseling guidance, equipped with basic needs, good social roles and can solve problems on their own.